Zuhud Versi Era Milenial dalam Perspektif Hadis: Sebuah Kajian pada Kitab Sunan at-Tirmidzi di Bab Zuhud - Hapiz Ilham Maulana; Alfian Febriyanto; Engkus Kusnandar; Aah Syafaah; Izzudin Izzudin (Gunung Djati Conference Series, 2023)
This study aims to discuss the millennial era version of zuhud in the perspective of hadith. This research uses a qualitative approach with descriptive-analytic method. The formal object of this research is the traditions about zuhud in Sunan at-Tirmidzi chapter Zuhud, while the material object of this research is the millennial era version of zuhud. The results and discussion of this study show that the millennial version of zuhud from the perspective of hadith can be extracted from the traditions of Sunan at-Tirmidzi chapter Zuhud in the hadith about early success in the hereafter, the hadith about the humiliation of the world before Allah and there is no comparison with the hereafter, and the hadith about hastening in goodness. This study concludes that the attitude of zuhun as an Islamic teaching exemplified by the Prophet PBUH which later became the forerunner of Sufism teachings can basically be realized in the form of a millennial era version through understanding and practicing hadith.